2009
DOI: 10.3200/jmbr.41.2.158-171
|View full text |Cite
|
Sign up to set email alerts
|

Global Information Pickup Underpins Anticipation of Tennis Shot Direction

Abstract: The authors examined the importance of local dynamical information when anticipating tennis shot direction. In separate experiments, they occluded the arm and racket, shoulders, hips, trunk, and legs and locally neutralized dynamical differences between shot directions, respectively. The authors examined the impact of these manipulations on resulting (display) dynamics and the ability of participants with varying perceptual skills to anticipate shot direction. The occlusion manipulation affected the display dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 45 publications
(84 reference statements)
12
131
0
5
Order By: Relevance
“…Thus, reliable visual perception of that movement is made possible by visual perception of these structures (cf. Huys et al, , 2009. It is by this process of perceiving dynamic structures that the tennis player could be provided with information for anticipating general outcomes of whole-body movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, reliable visual perception of that movement is made possible by visual perception of these structures (cf. Huys et al, , 2009. It is by this process of perceiving dynamic structures that the tennis player could be provided with information for anticipating general outcomes of whole-body movements.…”
Section: Discussionmentioning
confidence: 99%
“…( 2008) and Huys et al (2009)). To generate new data, u(t), for the simulations we computed the product of the projections ξ k (t) and the eigenvectors of mode 1 to 54, resulting in a 54-dimensional vector u(t) representing the dynamics corresponding to the 18 marker locations in 3 Cartesian directions.…”
Section: Apparatus and Stimulus Productionmentioning
confidence: 97%
“…First, Williams, Hodges, North, and Barton (2006) showed that it is rather specific relational information between certain key players that provide crucial information for superior recognition in soccer. Second, several studies provide evidence for the superiority of experts in picking up, for example, subtle kinematic cues when attempting to recognise and anticipate the outcome of an opponents action (e.g., Abernethy & Zawi, 2008;Huys et al, 2009;). …”
Section: Discussionmentioning
confidence: 99%
“…La zona que comprende el brazo efector ha sido considerada como altamente informativa en diversas investigaciones realizadas en modalidades deportivas abiertas, ya que su oclusión o neutralización ha producido un descenso en la precisión tanto de expertos como de novatos (e.g. Ward, Williams, & Bennett, 2002;Huys et al, 2009;Bourne, Bennett, Hayes, Smeeton, & Williams, 2013). Concretamente la zona de CM también se ha destacado en otras investigaciones realizadas sobre la acción del bloqueo en voleibol (e.g.…”
Section: C D D E P O R T Eunclassified